A National Analysis on Predictors of Discharge to Rehabilitation After Corrective Surgery for Adolescent Idiopathic Scoliosis. Issue 2 (15th January 2019) - De la Garza Ramos, Rafael; Nakhla, Jonathan; Echt, Murray; Schulz, Jacob F.; Gomez, Jaime A.; Cho, Woojin; Yassari, Reza
Abstract : Study Design: Retrospective study of a national database. Objective: To identify the incidence and risk factors for discharge to a rehabilitation facility after corrective surgery for adolescent idiopathic scoliosis (AIS). Summary of Background Data: The vast majority of patients who undergo surgery for AIS are discharged home, with limited data on rates and causes for discharge to a rehabilitation facility. Methods: The United States National Inpatient Sample (NIS) database was queried for the years 2012 to 2014. Inclusion criteria were children aged 10 to 18 who underwent surgery for idiopathic scoliosis. Studied data included patient demographics, operative parameters, length of stay, and hospital charges. Perioperative complications were also examined, along with their association with discharge to an inpatient rehabilitation facility. Statistical analysis was performed via chi-squared testing and multivariate analysis, with significance defined as a P -value <0.05. Results: A total of 17, 275 patients were included (76.3% female, mean age 14 yr). Out of the entire cohort, 4.8% of patients developed a complication and 0.6% were discharged to a rehabilitation facility. The most common complications included respiratory failure (2.3%), reintubation (0.8%), and postoperative hematoma (0.8%). Following multivariate analysis, male sex (Odds ratio (OR) 4.7; 95% Confidence Interval (CI), 1.8–12.2; P = 0.002), revision surgery (OR 29.6; 95% CI, 5.7–153.5; P < 0.001), and development of a perioperative complication (OR 12.3; 95% CI, 4.7–32.4; P < 0.001) were found to be significant predictors of discharge to rehabilitation. Average length of stay was 8 ± 6 versus 5 ± 3 days and hospital charges were 254, 425 versus 186, 273 in the complication and control groups, respectively (both P < 0.001). Conclusion: Discharge to rehabilitation after AIS surgery is uncommon. However, patients who are male, undergo revision procedures, or develop a complication may have a higher risk of a non-routine discharge. Complication occurrence also resulted in significantly longer lengths of stay and healthcare costs. Level of Evidence: 3 Abstract : Discharge to rehabilitation after corrective surgery for adolescent idiopathic scoliosis is very uncommon. In this national investigation, we found that male patients, patients undergoing revision procedures, and patients who developed a complication were at a higher risk for a non-routine discharge.